Multicriteria valuation of commercial construction projects for investment purposes - Zavadskas, Edmundas Kazimieras; Ustinovichius, Leonas; Stasiulionis, Andrius (Journal of Civil Engineering and Management, 2004)
The article provides the analysis of market development of commercial property constructions, trends, regularities, optimal site locations, characteristics of constructive selection of combinations, of the main financial investment indices after the change of political, economical and social relationships in the East Europe. The overview of the main modern investment requirements important for construction of commercial objects in order to get the maximum profit for exploitation thereof is provided. The models of choosing such indices as market research, site location, constructive combinations, financing of commercial objects are provided. It is emphasised that multiple criteria decision methods are most suitable, and particularly ELECTRE III for research and valuation of investment project alternatives of commercial objects is singled out.First Published Online: 14 Oct 2010